2021
DOI: 10.1017/jme.2021.81
|View full text |Cite
|
Sign up to set email alerts
|

The Dizziness of Freedom: Understanding and Responding to Vaccine Anxieties

Abstract: The rise in vaccine hesitancy in high-income countries has led some to recommend that certain vaccinations be made compulsory in states where they are currently voluntary. In contrast, I contend that legal coercion is generally inappropriate to address the complex social and psychological phenomenon of vaccine anxieties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 86 publications
0
3
0
2
Order By: Relevance
“…Dessa forma, a não adesão à vacinação causa impactos na esfera individual, que variam entre adoecimento, hospitalização e óbito, mas sobretudo em âmbito coletivo, pois o sucesso da vacinação demanda a participação de 80% da população 31 . Os grupos antivacina têm reforçado a ideia de que os pais têm direito de não vacinar seus filhos, concebendo direitos humanos como ausência de interferência, o que contrasta com o direito internacional que conceitua os direitos humanos positivamente 32 . A saúde é definida pela OMS 33 como um estado de completo bem-estar físico, mental e social, e não apenas ausência de doença ou enfermidade.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Dessa forma, a não adesão à vacinação causa impactos na esfera individual, que variam entre adoecimento, hospitalização e óbito, mas sobretudo em âmbito coletivo, pois o sucesso da vacinação demanda a participação de 80% da população 31 . Os grupos antivacina têm reforçado a ideia de que os pais têm direito de não vacinar seus filhos, concebendo direitos humanos como ausência de interferência, o que contrasta com o direito internacional que conceitua os direitos humanos positivamente 32 . A saúde é definida pela OMS 33 como um estado de completo bem-estar físico, mental e social, e não apenas ausência de doença ou enfermidade.…”
Section: Discussionunclassified
“…Os grupos antivacina têm reforçado a ideia de que os pais têm direito de não vacinar seus filhos, Cad. Saúde Pública 2023; 39(10):e00159122 concebendo direitos humanos como ausência de interferência, o que contrasta com o direito internacional que conceitua os direitos humanos positivamente 32 . A saúde é definida pela OMS 33 como um estado de completo bem-estar físico, mental e social, e não apenas ausência de doença ou enfermidade.…”
Section: Discussionunclassified
“…A meta-analysis of COVID-19-related VH using a socioecological model found that VH has been influenced at multiple levels and presented within chronological, macro-, and microsystems (Al-Jayyousi et al, 2021). Benbow's (2021) comparative literature review determined that little evidence existed on how VH affects family and social unit functioning amid new social and political contexts that impose coercive measures against nonvaccination. Further, limited data were available on how COVID-19 has influenced relationships and behaviors when individuals refuse vaccination, despite its well-publicized benefits.…”
Section: Gaps In the Literature And Rationalementioning
confidence: 99%
“…Further, limited data were available on how COVID-19 has influenced relationships and behaviors when individuals refuse vaccination, despite its well-publicized benefits. While political attitudes, education, critical literacy proficiency, and socioeconomic status all influence perspectives on vaccination, it is unclear how culturally aligned family values systems have interacted with COVID-19 vaccination decisions (Benbow, 2021).…”
Section: Gaps In the Literature And Rationalementioning
confidence: 99%
See 1 more Smart Citation